Pelaksanaan Tugas Pokok dan Fungsi Guru Pembimbing Khusus Di Sekolah Inklusi di Kota Padang - Aulia, Rahmi (RC-INSTITUT, 2019)
Abstract This research discusses the main tasks and functions of special supervising teacher in carrying out their duties. The background raised this issue because there is only one special supervising teacher to guide 20 students. Meanwhile, child with special needs require the role of a special supervising teacher. This research aims to find out how special supervising teacher deals with 20 students. This research used descriptive qualitative method. Data collection techniques using, observation, interviews, and documentation. The results of this research can be concluded that, the way of this special supervising teacherin guilding the students is by asking the grade teacher to help her in guiding child with special needs or with the help of special supervising teacher who have been personality provided by the parents of their students.The special supervising teacher cooperates with the various parties involved to support the implementation of students?s learning. When the students doesn?t have a personal special supervising teacher, the teachers from the school will guide the child alternately. Keywords: main tasks, function, special tutor